Aspectos do Crescimento e Influência de Parâmetros Físicos na atividade da lacase fungo Amazônico, Trametes lactinea (Berk) - Andrade , Ângela Lúcia Carvalho de (2011)
The application of basidiomycetes in different sectors of industry and biotechnology is increasing significantly due to its use in a wide range of areas, including chemical, food, fuel, agriculture, paper, textiles, cosmetics, pharmaceuticals and more. These fungi also have an essential role in the ecology of forests and their involvement in the regulation of energy and nutrient flow are of unique importance for these ecosystems. However, due to poor knowledge of unexplored Brazilian biodiversity, especially in the Amazon region, this research aimed to study the Amazonian strain (UEA_10202) of the fungus Trametes lactinea. This work aimed to study the influence of three culture media (abricó, potato and cupuaçu residual) in biomass production and secretion of fungal laccase from T. lactinea. The fungus showed the highest mycelial growth at pH 4 and lower at pH 9. So much for higher biomass production as for maximum activity of laccase was obtained in medium supplemented with “cupuaçu residual” The condition of agitation and the presence of inducer did not affect the biomass of T.lactinea. As for the production of laccase agitation positively affected the activity of this enzyme for the fungus T. lactinea. In relation to this inducer ethanol had a negative effect on laccase production from Trametes lactinea in all media and conditions tested. The results showed that both biomass production and laccase activity were influenced by the nutrients present in the culture media of the fungus Trametes lactinea.